Kemiskinan dalam Novel Di Kaki Bukit Cibalak Karya Ahmad Tohari - Dewi Ratnaningsih (Edukasi Lingua Sastra, 2017)
Literature is the most optimal meda to express idea of a writer. The ideas could be on the form of feedback, critic, satire, or the reaction. The literature is the mirror of society life, so that there are some life point of views included on the novel "Di Kaki Bukit Cibalak" by Ahmad Tohari. Ahmad Tohari is very great in expressing poverty reality occurs in 1970 in this novel. The description of poverty in this novel are described on the poverty of society life. In this novel, society were prefer eating cassava than rice. They did not also have good/proper house. In the novel, the actor Mbok Rolem has only one clothes. What Ahmad Tohari described on the novel is also experienced by Indonesian on 1970 until now.